2021
DOI: 10.7150/ijms.49328
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125b promotes migration and invasion by targeting the vitamin D receptor in renal cell carcinoma

Abstract: Purpose: To investigate the expression of miR-125b and vitamin D receptor (VDR) in renal cell carcinoma (RCC) and assess the biological function of miR-125b in RCC. Methods: We used quantitative real-time polymerase chain reaction (RT-PCR) to detect the expression of nucleic acids and western blotting to analyze the protein abundance in RCC cell lines. MiR-125b mimic and inhibitor were employed to investigate the function and behavior of miR-125b in RCC cell lines. The relationship between miR-125 and VDR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…miR-125a was significantly downregulated in breast and gastric cancer, and miR-125a substantially inhibited cancer cells' proliferation, migration, and invasion activities. [27][28][29] There is only one study showing an association between miR-125b and CSCs. Zhoug et al determined that miR-125b negatively correlated with CD133 expression in hepatocellular carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…miR-125a was significantly downregulated in breast and gastric cancer, and miR-125a substantially inhibited cancer cells' proliferation, migration, and invasion activities. [27][28][29] There is only one study showing an association between miR-125b and CSCs. Zhoug et al determined that miR-125b negatively correlated with CD133 expression in hepatocellular carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Çaykara et al ( 27 ) indicated that abnormally downregulated miR-124 was associated with the tumor stage, tumor size and neutrophil count in patients with RCC, and restoration of miR-124 expression may be effective in the treatment of RCC. He et al ( 28 ) reported that miR-125b was significantly upregulated in RCC tissues, which was negatively correlated with vitamin D receptor (VDR) levels. Through mediating VDR, miR-125 is capable of enhancing proliferative and migratory rates of RCC cells, suggesting miR-125 may be a potential therapeutic target of RCC.…”
Section: Discussionmentioning
confidence: 99%